Lingwizm w poezji współczesnej jako kategoria odbiorcza - Skibski, Krzysztof (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The article offers a proposal for the studies into a particular receptive disposition (derived from the phenomenon of Polish linguistic poetry) as a consequence of recognition of the special structure of a modern poem. The poetics of reception, rooted in theoretical tradition, when juxtaposed with reflection on the structure of verse and in connection with an epistemological value of a metaphor (as a notional construct) may motivate methodological (linguistic) considerations focused on language fundamentals for the reception of poetic texts. Apart from the general presentation of the topic, the article also includes an analytical sample, which deals with the phenomenon of parallelism in modern poetry. This parallelism is an effect of ellipsis in the verse, created in close connection with the poem’s construction and the reader’s reception competence.